(untitled) (Swiss Medical Weekly, 2017)
Iron deficiency is a prevalent and clinically relevant comorbidity in up to 50% of patients with chronic heart failure (CHF). Iron deficiency in CHF patients is associated with impaired quality of life, reduced exercise capacity and increased mortality, irrespective of the presence of anaemia. It is diagnosed by determining circulating ferritin levels and transferrin saturation. Three randomised trials (CONFIRM-HF, FAIR-HF, and EFFECT-HF) of intravenous ferric carboxymaltose in the treatment of iron deficiency in CHF patients with reduced left ventricular ejection fraction demonstrated improvement of symptoms, functional capacity and quality of life. These beneficial effects were independent of the presence of anaemia. In addition, CONFIRM-HF and subsequent meta-analyses indicated that treatment of iron deficiency may reduce the rate of hospitalisations for worsening CHF. Oral iron is available at lower cost than intravenous iron, but its use did not translate into beneficial effects in CHF patients with iron deficiency. Large randomised trials designed to assess long-term clinical outcomes of iron treatment in CHF patients are pending. Current guidelines advise establishing evidence-based pharmacological and device therapy to improve symptoms and prognosis in patients with CHF. In addition, screening for iron deficiency is recommended. Intravenous ferric carboxymaltose should be considered for treating iron deficiency in ambulatory symptomatic patients with reduced left ventricular ejection fraction in order to alleviate heart failure symptoms, and to improve exercise capacity and quality of life.